Terapi Bekam Basah guna Memperbaiki Status Hemodinamik pada Pasien Hipertensi - Sucipto, Adi; Fadlilah, Siti; Muflih, Muflih (Universitas Faletehan, 2023)
The increasing number of patients and the threat of complications make hypertension need to be watched. Non-pharmacotherapeutic treatment of hypertension can implement wet cupping therapy. This study aimed to determine the effects of wet cupping on the pulse and blood pressure of hypertensive patients. This research used a quasi-experimental method with pretest and posttest control group design. The samples consisted of control and intervention group consisting of 40 respondents in each and were selected by consecutive sampling technique. Wet cupping intervention was carried out once by a nurse as an assistant. The instrument used standard operating procedures, cupping tools, a digital sphygmomanometer, and an observation sheet. The statistical test used paired t-test and Wilcoxon test. The difference test used independent t-test and Mann Whitney. The control group experienced an increase in pulse and diastolic (3.98 times/minute and 1.77 mmHg), while the systolic was decreased (5.9 mmHg). The intervention group experienced a decrease in pulse, systolic and diastolic (1.05 times/minute, 8.13 mmHg, and 3.75 mmHg). The bivariate test in control group on the pulse, systolic, and diastolic variable showed p value of 0.035, 0.773, and 0.106. The bivariate test in the intervention group on the pulse, systolic, and diastolic variable showed p value<0.001, <0.001, and 0.001. The difference test on the pulse, systolic, and diastolic variable obtained p value of 0,057, 0.003, and 0.079. Cupping therapy effectively reduces hypertensive patients' pulse and blood pressure so that it can be used as an inexpensive therapeutic option.